PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA TANGERANG SELATAN - Susanti, Rini; Mardiana Yulianti, R.R. (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of work discipline and work motivation on employee performance at the South Tangerang City Education and Culture Office. The results show that there is an influence of training on employee performance at the South Tangerang City Education and Culture Office. It is shown that the correlation coefficient value of 0.576 has a moderate level of influence and the coefficient of determination (R2) is 33.2%. The t value of the Training variable is 5.687 which is greater than the t table value of 1.977 with a significance level of 0.0 which is smaller than 0.05 then it can be interpreted that Ha is accepted and H0 is rejected, so it can be concluded that Training has a positive and significant effect on employee performance. There is an influence of Career Development on the Performance of Employees of the South Tangerang City Education and Culture Service as indicated by a correlation coefficient of 0.739 with a strong relationship level and a coefficient of determination (R2) of 54.7%, the tcount value of the Career Development variable is 8.855 which is greater than the ttable of 1.977 with a significance level of 0.0 which is smaller than 0.05, so it can be interpreted that Ha is accepted and H0 is rejected. So it can be concluded that Career Development has a significant effect on Employee Performance. There is an influence of Training and Career Development on Employee Performance at the South Tangerang City Education and Culture Service. Proven by the regression equation Y = 9.819 + 0.112 X1 + 0.670 and the significance value is 0.0 while the Ftable value is 3.140. So it can be concluded that Fcount > Ftable (39.826>3.140) and significance < 0.05 (0 <0.05), then Ha is accepted, so it can be concluded that Training and Career Development together influence employee performance.